AMPUTATION REVISION IN AN ASIAN REHABILITATION CENTRE - Richard J Schwarz (Journal of Nepal Medical Association, 2004)
A retrospective study was carried out of amputation revisions performed at Green Pastures Hospital and Rehabilitation Centre between Jan 1990 and April 2004. The purpose was to determine the reasons for revision and whether these were preventable, and as well assess the outcome of the revision itself. A total of 26 revisions were performed; in 18 cases the primary amputation had been performed at another centre. The primary amputations were due principally to trauma, vascular disease and complications of leprosy. A poorly formed stump was the most common indication for revision (9), followed by recurrent ulceration (5) and infection (3). In 16 cases the need for revision was probably preventable. Only one patient required an amputation at a higher level. Prior to revision only one patient was able to wear a prosthesis; all but one patient were able to ambulate with their prosthesis following revision in a median time of eight weeks. Amputation revision in a rehabilitation centre has a high success rate in ambulation with a low complication rate. Greater attention to detail during the primary amputation will prevent the need for revision in many cases.